Incidence and host preference of red pumpkin beetle, Aulacophora foveicollis (Lucas) on cucurbitaceous vegetables - Kamal, M. M.; Uddin, Mohammad Mahir; Shahjahan, M.; Rahman, Md. Mahbubur; Alam, M. J.; Islam, M. S.; Yusop, Mohd Rafii; Latif, Mohammad Abdul (Marsland Press, 2014)
Three cucurbitaceous vegetables viz. sweet gourd (BARI Misti Kumra-1, BARI Misti Kumra-2 and Local Misti Kumra), bitter gourd (BARI Karola-1, Taj Karola-88 and Local Karola) and bottle gourd (BARI Lau-3, BARI Lau -4 and Local Lau) were selected to conduct a research on the incidence and host preference of red pumpkin beetle. In the field experiment at all the three stages, the highest incidence of red pumpkin beetle per plant was observed on sweet gourd and lowest on bitter gourd. The maximum number of beetle was observed on Local Misti Kumra at all the three stages and the lowest number of beetle was found on BARI Karola-1 at seedling stage and on Taj Karola-88 at flowering stage and on Local Karola at fruiting stage in the field. In net cage experiment, the highest and lowest number of beetle was also observed on sweet gourd and bitter gourd respectively. In the net cage among the nine varieties, the maximum number of beetle was observed on Local Misti Kumra. At all the three stages the highest percentage of leaf infestation was found on sweet gourd and the lowest on bitter gourd in the field. Among the nine varieties, the highest percentage of leaf infestation was recorded on Local Misti Kumra at all three stages in the field. The highest food consumption was recorded on sweet gourd among the crops and the highest leaf area damage was found on Local Misti Kumra in net cage experiment among the nine varieties. Among three cucurbit crops the total and daily food consumption was found highest on sweet gourd in the laboratory. The total and daily food consumption was the highest on Local Misti Kumra whereas the lowest was recorded on Local Karola among the nine varieties.